Effect of Proteolytic Enzymes on the Biological Degradability of Gelatin-Based Films - Bakyt B. Tyussyupova, Sagdat M. Tazhibayeva, Kuanyshbek Musabekov, Yessengeldi Mussatay, Azymbek Kokanbaev (International Journal of Advanced Science and Technology, 2020)
Biodegradable films based on gelatin were obtained. Glycerine is used as a plasticizer of films. The effect of proteolytic enzymes: pepsin and chymosin on the biodegradability of films was studied. It is shown that the specific activity of pepsin in relation to gelatin films is higher than that of chymosin. Structural and mechanical characteristics of gelatin films in the presence of pepsin and chymosin were determined. It is shown that with an increase in the concentration of enzymes, the strength, modulus of elasticity and deformation increase, which indicates the softening and decomposition of films. The destructive effect of enzymes on gelatin films is also shown by the change in the roughness of the films, which increases in the presence of enzymes, especially in the case of pepsin.